PENGARUH MOTIVASI, KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. BAKRIE PIPE INDUSTRIES - Safira Azzahra; Alnisa Min Fadlillah (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This research uses quantitative methods to the determine effect of motivation, compensation, and work satisfaction on employee performance objectively and systematically. This study uses the object of employees of PT Bakrie Pipe Industries. The population used are 156 people with a random sample using the Slovin formula as many as 112 respondents. Data were collected throughquestionnaires distributed to employees of PT Bakrie Pipe Industries using the Google Form application. Testing of the data in this study using the SmartPLS 3.0 test application. The series of test processes carried out resulted in the conclusion that 1) there is a positive and significant effect on motivation on employee performance, 2) there is a positive and significant effect oncompensation on employee performance, 3) there is a positive and significant effect on work satisfaction on employee performance, and 4) ) there is a positive and significant effect on motivation, compensation, and work satisfaction simultaneously on employee performance. Keywords: Work Environment, Work Stress, Work Discipline, Employee Performance,Management, and Human Resource Management